Simulation of a LiBr Absorption Solar Cooling System and Global Warming Impact Estimation - Kalogirou, Soteris A.; Florides, Georgios A. (My University, 2002)
The objective of this paper is to present the modelling of a complete lithium bromide (LiBr)-water absorption system and perform a global warming impact assessment. The system is modelled with the TRNSYS simulation program and the typical meteorological year file containing the weather parameters for a hot climate (Nicosia, Cyprus). Initially the LiBr cooler is modelled in order to derive the polynomial equations to be used in the TRNSYS deck file. These equations relate the unit capacity with the solution heat exchanger exit temperature, the coefficient of performance and the generator heat. The system considered employs a compound parabolic type collector 15 m2 in area, sloped at 30° and a storage tank size of 600 lt. Subsequently the global warming impact of the system is evaluated by estimating the total equivalent warming impact (TEWI) of the system in comparison to a system utilising a conventional R-22 air conditioner. The TEWI of the solar assisted system is about 107,200 kg CO2 and is lower than that of a conventional R-22 air conditioner system, which is 132,800 kg of CO2.
Keywords: Lithium bromide; Water absorption system